Studies on Identification and Classification of the Best Communities That Ensure the Mastery of Their Expenditure by Using the Threshold of Their Cluster - Solh, Anouar Riad; Belkacemi, Mourad El (New Visions in Science and Technology Vol. 6, 2021)
In the context of the rationalization of expenditure of local communities, we have developed a technique for segmentation of local communities according to their revenue ratios by using the algorithms of data mining, and identifying in the first place, their weight to control expenditure in their cluster. The latter is characterized by a threshold dependent on the number of its elements. In a second level, we built a new reorganization in their classification in order to increase the weight and subsequently to ensure better control and good management of local communities spending. The rationalization of public expenditures will be effective at the national level unless it is established at the regional level.